Identifying outcome domains to establish a core outcome set for progressive pulmonary fibrosis: a scoping review - Anouk Delameillieure; Vivien Somogyi; Silja Schenk; Nur Toreyin; Nikola Stenzel; Liesbet Van Bulck; Sofie Breuls; Michael Kreuter; Wim A. Wuyts; Nesrin Mogulkoc; Jeanette Boyd; Steve Jones; et al. (European Respiratory Review)
Introduction People with idiopathic pulmonary fibrosis (IPF) and other forms of progressive pulmonary fibrosis (PPF) have a high symptom burden and a poor health-related quality of life (HRQoL). Despite efforts to offer specialised treatment, clinical care for these patients remains suboptimal and several nonmedical needs remain unaddressed. Developing a core outcome set (COS) can help to identify a minimum set of agreed-upon outcomes that should be measured and acted-upon in clinical care. Aim As a first step towards developing a COS for IPF/PPF, we aimed to identify outcome domains investigated in IPF/PPF research. Methods Conducted within the COCOS-IPF (Co-designing a Core Outcome Set for and with patients with IPF) project, this scoping review follows Joanna Briggs Institute methodology and PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) guidelines to search PubMed, Embase and Web of Science for quantitative, qualitative and mixed-methods papers. We extracted each paper's outcomes verbatim and classified them using the COMET (Core Outcome Measures in Effectiveness Trials) taxonomy. Then, the research team structured outcomes or concepts with similar meanings inductively into outcome domains. Results We included 428 papers, extracting 1685 outcomes. Most outcomes (n=1340) were identified in quantitative sources, which we could classify in 64 outcome domains, with the main domains being “all-cause survival” (n=237), “lung function” (n=164) and “exercise capacity” (n=99). Qualitative sources identified 51 outcome domains, with the most frequent being “capability to do activities you enjoy” (n=31), “anxiety, worry and fear” (n=26) and “dealing with disease progression” (n=25). Conclusions The identified outcomes, spanning diverse domains, highlight the complexity of patient experiences and can form the basis to develop a COS for IPF/PPF clinical care, as well as future research.